Systemic Lupus Erythematosus Presenting as Myopericarditis with Acute Heart Failure: A Case Report and Literature Review - Richard Jesse Durrance; Malahat Movahedian; Worku Haile; Katerina Teller; Richard Pinsker (Case Reports in Rheumatology)
Acutely decompensated dilated cardiomyopathy in a middle-aged patient without the typical risk factor profile presents a clinical dilemma. While cardiomyopathy is a known aspect of systemic lupus erythematosus (SLE), initial clinical presentation as decompensated dilated cardiomyopathy (DCM) is exceedingly rare in the literature. We share the case of a 49-year-old African-American female with no past medical history who presented with overt heart failure of 4 weeks evolution. Workup showed acute onset decompensated dilated cardiomyopathy, with a serologic profile compatible with SLE. She responded well to immunosuppressive steroid therapy. Literature review for SLE presenting as dilated cardiomyopathy with acute heart failure revealed a paucity of clinical evidence and consensus. Therefore, a comprehensive review of case reports was undertaken. A total of 10 cases were identified. Patients were 90% female and averaged 31 years of age. Dyspnea was the most common clinical presentation, and dilated cardiomyopathy with severely compromised left ventricular function was universally appreciated. Clinical presentation to diagnosis averaged 2 weeks. Immunosuppressive therapy regimens were universally employed; however, the regimens varied significantly. High-dose steroid therapy was most commonly used, and clinical and functional recovery was reported in 90% of individual case reports. Within the limited evidence and experience of therapeutic approaches, the efficacy of different singular or combined therapy is based solely on anecdotal case reports. Given the near-complete response to a short course of high-dose steroid therapy as much in the clinical recovery as in the resolution of DCM, the limited evidence based on review of these observational case studies and series supports the initial use of high-dose steroid therapy in acute lupus myocarditis.